The usefulness of Mini Clinical Evaluation Exercise as a learning tool in different pediatric clinical settings - Goel, Atul; Singh, Tejinder (International journal of applied and basic medical research, 2015)
Background: Mini Clinical Evaluation Exercise (Mini-CEX), have been an underutilized tool for the formative assessment in India. Not many studies have been done in India to examine its feasibility and acceptability in residency programs of most clinical subjects. Aim: To assess the feasibility and acceptability of Mini-CEX in different pediatric clinical settings and to know if it helped the residents with improved learning. Methods: Pediatric residents were regularly evaluated with Mini-CEX over a period of 1 year by standard methodology. Each encounter was followed by case specific feedback given to the residents. Several such encounters were held in different pediatric clinical settings like pediatric outpatient departments (POPDs), pediatric wards, Pediatric Intensive Care Unit (PICU), Neonatal Intensive Care Unit (NICU), etc. By the end of the year, both teachers and residents were asked to give feedback on 5 point Likert scale based on their experience with the exercise. Results: The entire exercise was participated by 11 teachers and 23 residents. Mini-CEX encounters were conducted in POPDs 38%, pediatrics ward 22%, PICU 19%, NICU 15%, and casualty 6%. The overall average score for all students was 5.65. An average improvement in scores by 1.9 points was observed over a period of 1 year all students and teachers felt that the exercise was feasible in most pediatric clinical settings. Students accepted that the feedback given by the teachers well and accepted that this feedback helped them with improved learning. Conclusions: Residents and teachers, both considered Mini-CEX as a feasible exercise. Residents accepted that the feedback after each exercise helped them in their learning.